Tanfīz Al-Tharīqah Al-Ihāiyyah Fī Ta'līm Al-Lugah Al-Arabiyyah - Chairani Astina (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2019)
Teaching methods have been established and continued to be of particular importance to the classroom teaching process. Therefore, educators have concentrated most of their research efforts throughout the current century on the different teaching methods and their benefits in achieving desirable educational outcomes for students at different educational levels. This interest in teaching methods has led to the spread of saying that (the successful teacher is only a successful way), and those who train teachers to train their students to use different teaching methods that achieve the objectives of teaching easily and successfully, therefore, the oldest definitions of the teaching method refers to being the easiest ways to teach and learn. The suggestopedia method consists of a set of educational recommendations derived from the suggestive science that Luzanov described as "science concerned with the systematic study of the irrational and unconscious influences, or both," to which humans respond continuously. The most prominent features of this method is the use of decor, furniture, and the special way to arrange the classroom, and the use of music and authoritarian behavior followed by the teacher during teaching.This method aims to remove or remove psychological barriers when students have trusted the teacher and themselves. In terms of language theory, this method does not direct the student to memorize vocabulary and acquire the habit of speech but to communicative practices. There are six basic principles of this method: authority, infantilization, dual comunication, intonation, rhythm, and semi-negative (Pseudo-passive).